Características clínicas-epidemiológicas de los pacientes adultos diabéticos tipo 2 con infecciones motivo de hospitalización. Hospital Belén de Trujillo, 2008-2014 - Paico Azcárate, Christian Peter (2016)
To determine clinical and epidemiological traits of adult type 2 diabetic patients with infections which led to hospitalization at Hospital Belén de Trujillo (HBT), Department of Internal Medicine, between years 2008 - 2014. Materials and Methods: A descriptive-transversal study was performed, comprising 169 medical records of hospitalized patients with type 2 diabetes mellitus from HBT´s Medical Department, who were classified as such based on clinical or bacteriological criteria at time of discharge. The study took place between years 2008-2014, and 158 out of 169 patients initially chosen met the inclusion and exclusion selection requirements for the study. Results and conclusions: The average age of patients in the study was 60.51 ± 10.85 years, there was a female gender predominance (55.70%) and Middle School completion as highest education achieved had the greatest prevalence among subjects tested (48.10%). The majority of patients in the study came from Trujillo district (41.14%). The most frequent reason of hospitalization was infection due to diabetic foot (36.12%). Most frequent signs and symptoms were those inherent to the organ or system compromised by the disease. Fever as a systemic sign was most often found among respiratory airway infections. The majority of patients had previous treatment with oral antidiabetic drugs at time of hospitalization (50%), had a prolonged time of illness (46.84%) and maintained an inadequate surveillance of serum glucose levels (88.61%)